Gabrielle’s Contribution to (WTO) Treaty Interpretation “building bridges” - Van Damme, Isabelle (Revue québécoise de droit international / Quebec Journal of International Law / Revista quebequense de derecho internacional, 2025)
Through her work at the World Trade Organization (WTO) Secretariat and in academia, Gabrielle Marceau has shaped the understanding of treaty interpretation in WTO law and its relationship to public international law. A central theme in her scholarship is the comparison between interpretive practices in WTO dispute settlement and the principles codified in the Vienna Convention on the Law of Treaties. The article highlights her focus on evolutionary interpretation, understood not as an abstract theory but as a practical method for adapting agreements to changing social, legal, and technical contexts. Gabrielle Marceau analyzed the tension between stability and change in WTO law and proposed a typology of evolutionary interpretation, including linguistic shifts, contextual evolution, technical or physical transformations, and changes in other relevant treaties or legal sources. She also examined how Appellate Body reasoning on issues such as “subsequent practice” has influenced, and been influenced by, other international courts and tribunals, creating a dialogue across regimes. By framing evolutionary interpretation as a tool to preserve the relevance and effectiveness of WTO agreements, Gabrielle Marceau’s work advocates a nuanced approach that bridges international trade law and broader public international law, enriching both fields.